Study on Attitudes and Barriers of Medical Students towards Conducting Research in a Medical College - Manjunath G. Narasimhaiah; Swamy R. Mallikarjuna; Riyaj A. Kalaburgi (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Background: It is well known that evidence-based medicine is the rule for clinical practice. This can be enhanced by conducting good research. Medical students, being the future doctors, should contribute significantly, but research among medical students is very poor with respect to presentations and publications. Objectives: To identify the various barriers, motivational factors and attitude for conducting research. Methods: This was a cross-sectional observational study involving 3 different batches of medical students by giving a semi-structured questionnaire. Results: The response among the participants to involve in research was only 30%. Among them, the overall attitude and barrier score were 3.69±0.29 and 3.63±0.42, respectively, with statistical significance being shown between genders and not between batches. The biggest barrier was a lack of previous research experience (91.67%). The most common motivational factor was self-interest (90.7%). Conclusions: If given sufficient training and facilities provided, we should be able to get more research done by the medical students.